Implementation of a Three-Dimensional Pedometer Automatic Accumulating Walking or Jogging Motions in Arbitrary Placement - Jia-Shing Sheu; Wei-Cian Jheng; Chih-Hung Hsiao (International Journal of Antennas and Propagation)
This study proposes a method for using a three-axis accelerometer and a single-chip microcontrol unit to implement a three-dimensional (3D) pedometer that can automatically identify walking and running motions. The proposed design can calculate the number of walking and running steps down to small numbers of steps and can be easily worn, thus remedying defects of generic mechanical and 3D pedometers. The user’s motion state is calculated using a walk/run mode switching algorithm.